2007
DOI: 10.1007/s10450-007-9027-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SBA-15/carbon composite with an ink-bottle-like pore structure by a novel pulse CVD technique

Abstract: A novel and easy post modification method, pulse chemical vapor deposition (pulse CVD), was developed to tailor the pore-opening of SBA-15 while largely keeping its surface area and pore volume. By using acetylene as carbon precursor and nitrogen as carrier gas, the poremouth of SBA-15 was effectively reduced from 8.1 nm to 5.1 nm within 5 min while maintaining the pore body at 8.1 nm. This ink-bottle-structured SBA-15/carbon composite only losses 12% BET specific surface area and 16% total pore volume, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The deposition of carbon on oxide supports has been noted by other researchers when starting with aqueous solutions of sugars, for use in photocatalysis or lithium ion batteries. However, our approach, which involves the controlled pyrolysis of sugar, is much simpler than the previously reported sugar and nonsugar methods used in carbon coating of oxides. In this work, we describe an unexpected benefit of the carbon coating on the stability of Pd nanoparticles under aqueous conditions. The support used to demonstrate Pd stability is a commercial silica obtained from Sigma-Aldrich.…”
Section: Introductionmentioning
confidence: 94%
“…The deposition of carbon on oxide supports has been noted by other researchers when starting with aqueous solutions of sugars, for use in photocatalysis or lithium ion batteries. However, our approach, which involves the controlled pyrolysis of sugar, is much simpler than the previously reported sugar and nonsugar methods used in carbon coating of oxides. In this work, we describe an unexpected benefit of the carbon coating on the stability of Pd nanoparticles under aqueous conditions. The support used to demonstrate Pd stability is a commercial silica obtained from Sigma-Aldrich.…”
Section: Introductionmentioning
confidence: 94%
“…Several synthesis strategies have been reported for coating silica mesopores with a carbon layer. Thus, Zhang et al [11] and He et al [12] reported modifying the size of the pore entrances of SBA-15 by depositing a carbon layer using a chemical vapor deposition technique. The usual procedure for preparing silica-carbon composites consists in attaching organic moieties to the silica surface followed by a carbonization step [13][14][15].…”
Section: Introductionmentioning
confidence: 99%